TINJAUAN YURIDIS TERHADAP PEMBATALAN PUTUSAN ARBITRASE BADAN PENYELESAIAN SENGKETA KONSUMEN DALAM PENERAPAN HUKUM (STUDI PUTUSAN: PUTUSAN PENGADILAN NEGERI TANGERANG NOMOR 149/PDT.SUS.BPSK/2016/PN.TNG) - Aloysius Ryantori; Gatot P Soemartono (Jurnal Hukum Adigama, 2021)
The sale and purchase agreement does not always run smoothly, there are disputes that occur between consumers and business actors. Dispute resolved through the Consumer Dispute Resolution Agency (BPSK). BPSK decisions are final and binding, and can be immediately implemented However, business actors often do not implement the results of the BPSK decision and file an objection to the District Court. The main problems are: 1) How is the implementation of the law Article 54 Paragraph 3 Law Number 8 of 1999 concerning Consumer Protection at decision number 149 / Pdt.Sus BPSK / 2016 / Pn.Tng in realizing the principle legal certainty? 2) How is the juridical analysis of the position of the verdict District Court number 149 / Pdt.Sus BPSK / 2016 / Pn.Tng received a verdict arbitration number 13 / BPSK-TANGSEL / XII / 2015 which is final and binding? The author examines this problem using the method normative legal research and uses a statutory approach, a case approach and a conceptual approach. Research data shows that the BPSK decision has no legal force still, because the Consumer Protection Law (UUPK) opens the option to submit an objection attempt to the District Court. As is the attempt to object to this authorizes the District Court to cancel the BPSK decision. The government should have immediately made more concrete regulations to clarify the existence of BPSK so that the results of BPSK decisions can be implemented more effectively.